2017
DOI: 10.1017/s0029665117000428
|View full text |Cite
|
Sign up to set email alerts
|

The future for long chain n-3 PUFA in the prevention of coronary heart disease: do we need to target non-fish-eaters?

Abstract: Dietary guidelines in many countries include a recommendation to consume oily fish, mainly on the basis of evidence from prospective cohort studies that fish consumption is cardioprotective. However, average intakes are very low in a large proportion of the UK population. Some groups, such as vegans and vegetarians, purposely omit fish (along with meat) from their diet resulting in zero or trace intakes of long chain (LC) n-3 PUFA. Although the efficacy of dietary fish oil supplementation in the prevention of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 136 publications
0
13
0
1
Order By: Relevance
“…In these experiments, we found that in response to high cholesterol concentrations, the expression of the HMGCS2 gene was significantly increased [4]. We also observed overexpression of HMGCS2 mRNA [6] in the liver of rats receiving a diet containing only saturated fats [23]. Extending previous works using an NMR-based metabolomics approach, we investigated the hypothesis of a possible correlation between the previously described transcriptomic signature of hepatoma cell lines treated with hypercholesterolaemic sera and the metabolomic signatures of the same sera [4].…”
Section: Plos Onementioning
confidence: 66%
“…In these experiments, we found that in response to high cholesterol concentrations, the expression of the HMGCS2 gene was significantly increased [4]. We also observed overexpression of HMGCS2 mRNA [6] in the liver of rats receiving a diet containing only saturated fats [23]. Extending previous works using an NMR-based metabolomics approach, we investigated the hypothesis of a possible correlation between the previously described transcriptomic signature of hepatoma cell lines treated with hypercholesterolaemic sera and the metabolomic signatures of the same sera [4].…”
Section: Plos Onementioning
confidence: 66%
“…N‐6 PUFA play a vital role in many physiological functions but there was still controversy concerning about its effect on CVD risk . Dietary guidelines in many countries included a recommendation to consume oily fish, mainly on the basis of evidence from prospective cohort studies that fish consumption was cardioprotective . There was a need for sustainable sources of biologically active n‐3 PUFA, and certain plants contained high concentrations of ALA .…”
Section: Discussionmentioning
confidence: 99%
“…A ratio below 4:1 improves cardiovascular outcomes and may inhibit cancer [20]. The relationship between dietary intake and circulating plasma levels is less obvious, because conversion of short chain omega-3 ALA (consumed in plants) into long chain EPA and DHA occurs in tight competition with the conversion of omega-6 fats into inflammatory hormones ( Figure 1) [21]. In a comparison of fish-eaters, meat-eaters, vegetarians, and vegans, meat-eaters had the lowest blood EPA level and vegans had the lowest DHA level, while fish-eaters had the highest DHA and second-highest EPA (behind vegans) [22].…”
Section: Vegetarian and Pescetarian Dietsmentioning
confidence: 99%
“…Both the inflammation-resolving and pro-inflammatory pathways use the same metabolic enzymes to compete for their respective polyunsaturated fatty acid (PUFA) substrates: Omega-3 ALA and omega-6 LA respectively. The ratio of omega-6: Omega-3 fats in Western, Mediterranean, and healthy plant-based diets can favor one pathway, having implications for cardiovascular disease (CVD)[21].Volume 6 • Issue 2 • 1000223 Health Care Current Reviews, an open access journal ISSN:2375-4273…”
mentioning
confidence: 99%